Ramucirumab versus placebo as second-line treatment in patients with advanced hepatocellular carcinoma following first-line therapy with sorafenib (REACH): a randomised, double-blind, multicentre, phase 3 trial. Issue 7 (July 2015) - Zhu, Andrew X; Park, Joon Oh; Ryoo, Baek-Yeol; Yen, Chia-Jui; Poon, Ronnie; Pastorelli, Davide; Blanc, Jean-Frederic; Chung, Hyun Cheol; Baron, Ari D; Pfiffer, Tulio Eduardo Flesch; Okusaka, Takuji; Kubackova, Katerina; et al.
Summary Background VEGF and VEGF receptor-2-mediated angiogenesis contribute to hepatocellular carcinoma pathogenesis. Ramucirumab is a recombinant IgG1 monoclonal antibody and VEGF receptor-2 antagonist. We aimed to assess the safety and efficacy of ramucirumab in advanced hepatocellular carcinoma following first-line therapy with sorafenib. Methods In this randomised, placebo-controlled, double-blind, multicentre, phase 3 trial (REACH), patients were enrolled from 154 centres in 27 countries. Eligible patients were aged 18 years or older, had hepatocellular carcinoma with Barcelona Clinic Liver Cancer stage C disease or stage B disease that was refractory or not amenable to locoregional therapy, had Child-Pugh A liver disease, an Eastern Cooperative Oncology Group performance status of 0 or 1, had previously received sorafenib (stopped because of progression or intolerance), and had adequate haematological and biochemical parameters. Patients were randomly assigned (1:1) to receive intravenous ramucirumab (8 mg/kg) or placebo every 2 weeks, plus best supportive care, until disease progression, unacceptable toxicity, or death. Randomisation was stratified by geographic region and cause of liver disease with a stratified permuted block method. Patients, medical staff, investigators, and the funder were masked to treatment assignment. The primary endpoint was overall survival in the intention-to-treat population. This study is registered with ClinicalTrials.gov, number NCT01140347. Findings Between Nov 4, 2010, and April 18, 2013, 565 patients were enrolled, of whom 283 were assigned to ramucirumab and 282 were assigned to placebo. Median overall survival for the ramucirumab group was 9·2 months (95% CI 8·0–10·6) versus 7·6 months (6·0–9·3) for the placebo group (HR 0·87 [95% CI 0·72–1·05]; p=0·14). Grade 3 or greater adverse events occurring in 5% or more of patients in either treatment group were ascites (13 [5%] of 277 patients treated with ramucirumab vs 11 [4%] of 276 patients treated with placebo), hypertension (34 [12%] vs ten [4%]), asthenia (14 [5%] vs five [2%]), malignant neoplasm progression (18 [6%] vs 11 [4%]), increased aspartate aminotransferase concentration (15 [5%] vs 23 [8%]), thrombocytopenia (13 [5%] vs one [<1%]), hyperbilirubinaemia (three [1%] vs 13 [5%]), and increased blood bilirubin (five [2%] vs 14 [5%]). The most frequently reported (≥1%) treatment-emergent serious adverse event of any grade or grade 3 or more was malignant neoplasm progression. Interpretation Second-line treatment with ramucirumab did not significantly improve survival over placebo in patients with advanced hepatocellular carcinoma. No new safety signals were noted in eligible patients and the safety profile is manageable. Funding Eli Lilly and Co.